Total synthesis and absolute configuration determination of Ktedonoketone, a benzenoid metabolite from Thermophilic bacterium - Dandawate, Monica; Choudhury, Rahul; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Tetrahedron Letters, 2020)
The successful total synthesis of both enantiomers of ktedonoketone allowed us to decipher an unambiguous assignment of absolute configuration of the natural product. The concise synthesis highlights Wacker oxidation and aldol condensation as key steps. In addition to this, the current synthetic route is suitable to access a library of compounds on the similar skeleton as one can use readily available amino acids and Grignard reagents as variants. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Absolute configuration; Ktedonoketone; Total synthesis; Wacker oxidation

Tuning of alpha-silyl carbocation reactivity into enone transposition: application to the synthesis of peribysin D, E-volkendousin, and E-guggulsterone - Athawale, Paresh R.; Zade, Vishal M.; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Organic Letters, 2021)
A reliable method for enone transposition has been developed with the help of silyl group masking. Enantio-switching, substituent shuffling, and Z-selectivity are the highlights of the method. The developed method was applied for the first total synthesis of peribysin D along with its structural revision. Formal synthesis of E-guggulsterone and E-volkendousin was also claimed using a short sequence.

Total synthesis of 12, 13-dibenzyl-banistenoside B and analogs - Patil, Suhag S.; Jachak, Gorakhnath R.; Krishna, Gamidi Rama; Argade, Narshinha P.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2022)
Banistenosides A and B possessing a unique ``azepino(1,2-a)tetrahydro-beta-carboline'' carbon framework were isolated from the stem of Banisteriopsis caapi and showed MAO-A inhibition. Herein, we report the total synthesis of dibenzyl derivative of the untouched natural product in the last two decades, Banistenoside B. The key steps involve construction of 6.5.6.7 tetracyclic core using Pictet-Spengler reaction and intramolecular amide coupling. The stereoselective glycation was achieved through Hotha's protocol using gold catalyst, and silver triflate in the late stage of synthesis. The stereochemistry of most of the essential compounds were confirmed by X-ray crystallography.
Keywords: Au-catalyst; Multiple steps total synthesis; Natural products; Pictet-Spengler reaction; Wittig reaction

Total synthesis and absolute configuration determination of the α-glycosidase inhibitor (3S,4R)-6-Acetyl-3-hydroxy-2,2-dimethylchroman-4-yl (Z)-2-Methylbut-2-enoate from Ageratina grandifolia - Dandawate, Monica; Choudhury, Rahul; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Journal of Natural Products, 2023)
Herein, we report the first total synthesis of & alpha;-glycosidaseinhibitor (3R, 4S)-6-acetyl-3-hydroxy-2,2-dimethylchroman-4-yl(Z)-2-methylbut-2-enoate as well as its enantiomer.Our synthesis confirms the chromane structure separately proposedby Navarro-Vazquez and Mata, on the basis of DFT computations. Furthermore,our synthesis allowed us to determine the absolute configuration ofthe natural compound as (3S, 4R)and not (3R, 4S).

Transfer semi-hydrogenation of terminal alkynes with a well-defined iron complex - Chowdhury, Deep; Goswami, Souvik; Krishna, Gamidi Rama; Mukherjee, Arup (Dalton Transaction, 2024)
The synthesis and characterization of a bis-iron(ii) complex was accomplished upon treatment of a phosphine free NNN-pincer ligand (L) with FeCl2 center dot 4H2O under ambient conditions. The deep greenish colored iron(ii) complex (Fe-1) was characterized by a single-crystal X-ray diffraction study along with IR spectroscopy, UV-Vis spectroscopy, mass spectrometry, and elemental analysis. The Fe-1 complex was tested for the transfer semi-hydrogenation of terminal alkynes to the corresponding alkenes through the dehydrogenation of dimethyl amine-borane. This procedure enables the conversion of various structurally different terminal alkynes to alkenes under mild conditions. Control experiments were performed to shed light on the possible intermediates generated during the present protocol. A bench stable iron(ii) complex with the pincer ligand backbone was synthesized and characterized. The well-defined iron complex was successfully utilized for the dehydrogenation of DMAB and subsequent transfer semi-hydrogenation of terminal alkynes.